2014
DOI: 10.1208/s12249-014-0242-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Comparison of Lidocaine-Tetracaine and Lidocaine-Camphor Eutectic Mixtures Based on Their Crystallization and Hydrogen-Bonding Abilities

Abstract: Abstract. Eutectic mixtures formed between active pharmaceutical ingredients and/or excipients provide vast scope for pharmaceutical applications. This study aimed at the exploration of the crystallization abilities of two eutectic mixtures (EM) i.e., lidocaine-tetracaine and lidocaine-camphor (1:1 w/w). Thermogravimetric analysis (TGA) for degradation behavior whereas modulated temperature differential scanning calorimetry (MTDSC) set in first heating, cooling, and second heating cycles, was used to qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…One of the requirements for eutectic mixture formation is that the components forming the mixture should have moieties that can interact to form noncovalent interactions [4], with a major presence of electrostatic interactions [42]. In the case of LOV and the selected carboxylic acids (Figure 1), the main interaction should occur between the carbonyl and hydroxyl groups present in both LOV and the carboxylic acids used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the requirements for eutectic mixture formation is that the components forming the mixture should have moieties that can interact to form noncovalent interactions [4], with a major presence of electrostatic interactions [42]. In the case of LOV and the selected carboxylic acids (Figure 1), the main interaction should occur between the carbonyl and hydroxyl groups present in both LOV and the carboxylic acids used.…”
Section: Resultsmentioning
confidence: 99%
“…Eutectic mixtures are multicomponent organic materials formed by two or more crystalline solids that are immiscible in the solid state and miscible in the liquid state [1,2]. Their formation occurs via noncovalent forces [3,4], mainly hydrogen bonding, ionic and van der Waals forces, and aromatic interactions [4]. In general, the melting temperature of the eutectic is lower than the melting temperatures of their parent components [5].…”
Section: Introductionmentioning
confidence: 99%
“…The study of the anti- Most API-DES reported to date exhibit melting temperatures near or below the human body's temperature and usually envisage topical and oral administration [18,83,84]. Initially, the majority of these liquid forms were designed for transdermal purposes and included permeation enhancers, such as terpenes and fatty acids [19,85,86]. In 1998, Stott and coworkers [83] reported a series of API-DES based on ibuprofen and different permeation enhancers, such as L-menthol, L-menthone thymol, D-limonene, 1,8-cineole and p-cymene.…”
Section: Api-des Formulationsmentioning
confidence: 99%
“…APIs, such as menthol, ibuprofen, lidocaine, itraconazole, cannabidiol and testosterone, were involved in the formation of API-based DESs, which maintained in the therapeutic effect of the APIs (Aroso et al, 2015;Aroso et al, 2016;Cordeiro et al, 2017;Duarte et al, 2017;Gala et al, 2015;Kaplun-Frischoff & Touitou, 1997;Lodzki et al, 2003;Morimoto et al, 2000;Park et al, 2012;Silva et al, 2019;Stott et al, 1998;Wang et al, 2017;Woolfson et al, 2000) (Figure 1, Table 1). Silva et al constructed hydrophobic DESs based on menthol and saturated fatty acids with different chain lengths, including stearic acid, myristic acid and lauric acid, and evaluated the toxicity and antibacterial activity of these DESs to human immortal keratinocyte line (HaCaT) cells (Silva et al, 2019).…”
Section: Api-based Dessmentioning
confidence: 99%